A kinetic study to recover valuables from hazardous ISF slag. Issue 4 (August 2020) - Leuchtenmueller, Manuel; Schatzmann, Walter; Steinlechner, Stefan
Abstract: The present paper investigates a reduction process using a carbon-saturated iron melt to treat an imerpial smelting furnace (ISF) slag. The process allows for the removal of heavy metals that are known to negatively impact the surrounding environment (Zn, Pb and As). The work includes a short characterization of the slag, describes the reductive metal bath process itself and finally, investigates the reaction kinetics of the process. Experiments show an almost complete removal of harmful elements from the slag and the possibility of the generation of marketable materials: A Zn- and Pb-rich flue dust, a utilizable slag, and an iron alloy. The produced flue dust has a similar composition as double washed Waelz oxide. The concentration of Zn, Pb, and As in the final slag phase was below 100 ppm corresponding to a recovery rate of > 99.9 % A kinetic model was developed describing the reaction rates of the carbothermic reduction reaction for FeO and ZnO. The temperature dependency of the reaction rate was found to follow the Arrhenius equation, the activation energies were determined to be 216 kJ/mol for ZnO and 191 kJ/mol for the FeO reduction reaction. Finally, mass transfer coefficients were calculated and visualized for both reactions.